Facile synthesis of superhydrophobic TiO2/polystyrene core-shell microspheres (eXPRESS Polymer Letters)
In this paper, core-shell TiO2/polystyrene (TiO2/PS) microspheres with superhydrophobic properties were prepared via a facile method. Our method needs neither special apparatus nor complicated chemical treatment. The whole process includes two steps: firstly, coupling agent was used to modify TiO2 by sol-gel method; secondly, fabrication of TiO2/PS dispersions was carried out via in-situ free-radical polymerization strategy. The component and structure of the TiO2/PS particles were characterized by Fourier transform infrared (FTIR) spectroscopy, thermogravimetric analysis (TGA), field emission scanning electron microscope (FE-SEM) and transmission electron microscopy (TEM). The TiO2 gel particles with average diameter of 1 μm exhibited irregular spherical shape and obvious aggregation. Compared with the TiO2 particles, the resulting TiO2/PS particulates showed regular spherical shape, better dispersion and bigger size. By directly depositing the resulted TiO2/PS dispersion on a Cu foil, the coating showed superhydrophobic property which was reflected by the contact angle (CA) of water on the surface with high water adhesion. The apparent CA of water is 153.5±1.5°, suggesting that this composite possesses well superhydrophobicity.